2021
DOI: 10.3390/biology10111187
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Customized Insoles on Gait in Post-Stroke Hemiparetic Individuals: A Randomized Controlled Trial

Abstract: Background: Insoles have been widely applied to many diseases, but stroke involves complex problems and there is a paucity of research on the application of insoles in stroke patients. Aim: To evaluate the effect of customized insoles on gait in patients with hemiplegia. Design: A randomized controlled trial. Setting: Rehabilitation department of a hospital. Population: A total of 50 stroke patients were randomized into an experimental group (n = 25) or a control group (n = 25). Methods: Both groups received c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 48 publications
2
15
0
Order By: Relevance
“…Three studies [ 41 , 42 , 43 ] (total n = 45) involved manipulating the surface under the feet, altering mechanical alignment and proprioceptive input, via changes in surfaces [ 41 ] or wearing bespoke insoles [ 42 , 43 ]. Study samples ranged from 16 (just eight in the experimental group) [ 41 ] to 50 (25 in the experimental group) [ 43 ], with the third study [ 31 ] only including a total of 24 participants (12 in the experimental, insoles group). The mean difference ranged from 0.00 m/s (95% CI –0.18, 0.18; d = 0.000) [ 42 ] for mean velocity to 16.8 m (95% CI –1.95, 35.55; d = 0.527) [ 43 ] for the six-minute walk test.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three studies [ 41 , 42 , 43 ] (total n = 45) involved manipulating the surface under the feet, altering mechanical alignment and proprioceptive input, via changes in surfaces [ 41 ] or wearing bespoke insoles [ 42 , 43 ]. Study samples ranged from 16 (just eight in the experimental group) [ 41 ] to 50 (25 in the experimental group) [ 43 ], with the third study [ 31 ] only including a total of 24 participants (12 in the experimental, insoles group). The mean difference ranged from 0.00 m/s (95% CI –0.18, 0.18; d = 0.000) [ 42 ] for mean velocity to 16.8 m (95% CI –1.95, 35.55; d = 0.527) [ 43 ] for the six-minute walk test.…”
Section: Resultsmentioning
confidence: 99%
“…Study samples ranged from 16 (just eight in the experimental group) [ 41 ] to 50 (25 in the experimental group) [ 43 ], with the third study [ 31 ] only including a total of 24 participants (12 in the experimental, insoles group). The mean difference ranged from 0.00 m/s (95% CI –0.18, 0.18; d = 0.000) [ 42 ] for mean velocity to 16.8 m (95% CI –1.95, 35.55; d = 0.527) [ 43 ] for the six-minute walk test.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, there was no obvious correlation between the BBS score and the stance phase, swing phase of the nonhemiplegic limbs, while the BBS score was negatively correlated with the stance and swing phases of the hemiplegic limbs and dual stance phase. Wang et al (2021) reported that as the pressure of hemiplegic forefoot in stroke-affected patients improved, the active dorsiflexion of the hemiplegic foot was promoted, the center of gravity was easier to move forward, the walking ability improved, and the balance ability improved. In et al (2017) improved the patient's knee extension ability, strengthened the contact area of the feet in the stance phase, and strengthened the dorsiflexion to reduce the time of the hemiplegic stance and swing phases, improve the patient's balance function, and improve their walking ability.…”
Section: Figurementioning
confidence: 99%